SEED: A software tool and an active-learning strategy for data structures courses (2018)
SEED is a software tool designed for Java consisting of a class library and a set of simulators to facilitate learning of the main data structures. The educational component is based on an active case-solving methodology accompanied by a pedagogical strategy. This strategy allows for the development of a multilayer-model-programming work for the construction of basic and advanced applications in real domains and for integration of its use, development and operation assessment with data structures. The evaluation results of SEED as a pedagogical mediator in the issue of binary trees is presented. The evaluation indicates that students prefer to use SEED due to its simplicity and attractive GUIs which facilitate data structures learning.